PERCEIVED FACTORS THAT INFLUENCE HABITUAL CONSUMPTION OF ALCOHOLIC DRINKS AMONG THE YOUTHS IN ANAMBRA STATE. ADA ANYAMENE (Journal of Guidance and Counselling Studies, 2016)
Consuming alcohol forms an important habitual social practice for the youths in many cultures despite the fact that it is harmful to the body. To gain more knowledge on the perceived factors that influence alcohol consumption among the youths in Anambra State, three research questions and one hypothesis guided the study. A descriptive survey was adopted. The population for the study comprised all the youths in Anambra State. Purposive sampling technique was used to select 1,495 youths in Anambra State. Two hundred youths were purposively selected for the study. Data were collected using youth alcohol consumption questionnaire (YACQ) and was analyzed using mean scores for the research questions and z-test for the hypothesis. Based on the analysis of the data, the following findings were made. Male youths in the State are aware of the perceived factors that influence habitual consumption of alcoholic drinks. Also the female youths are aware of the perceived factors that influence habitual consumption of alcoholic drinks in Anambra State. The implication for counselling were discussed and the study made a number of recommendations and suggestions for further research.